2016
DOI: 10.1007/s00706-015-1653-y
|View full text |Cite
|
Sign up to set email alerts
|

Drugs from nature targeting inflammation (DNTI): a successful Austrian interdisciplinary network project

Abstract: Inflammation is part of numerous pathological conditions, which are lacking satisfying treatment and effective concepts of prevention. A national research network project, DNTI, involving scientists from six Austrian universities as well as several external partners aimed to identify and characterize natural products capable of combating inflammatory processes specifically in the cardiovascular system. The combined use of computational techniques with traditional knowledge, high-tech chemical analysis and synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
0
16
0
1
Order By: Relevance
“…These results showed that the affinity of tocotrie-nol analogues to microsomal prostaglandin E 2 synthase-1 most probably contributes to the anti-inflammatory potential of this class of derivatives. [8], a comprehensive in silico pharmacophorebased virtual screening of T3 derivatives isolated from Garcinia amplexicaulis Vieill. ex Pierre (Clusiaceae) [9] was performed.…”
mentioning
confidence: 99%
“…These results showed that the affinity of tocotrie-nol analogues to microsomal prostaglandin E 2 synthase-1 most probably contributes to the anti-inflammatory potential of this class of derivatives. [8], a comprehensive in silico pharmacophorebased virtual screening of T3 derivatives isolated from Garcinia amplexicaulis Vieill. ex Pierre (Clusiaceae) [9] was performed.…”
mentioning
confidence: 99%
“…Preparative HPLC was carried out on a Phenomenex Luna reversed-phase column (10 µm C18(2) phase, 100 A; 250 mm × 21.20 mm ID, (Phenomenex, Aschaffenburg, Germany), and separations were performed using a Shimadzu LC-8A device (SIL-10AP autosampler, SPD-20 detector, and FRC-10A fraction collector (Shimadzu Österreich, Korneuburg, Austria). NMR spectra were recorded from CDCl 3 or DMSO-d 6 A round bottomed flask was charged with 3,4,5-trimethoxybenzaldehyde (25 g, 127.4 mmol, 1 equiv.) under argon atmosphere.…”
Section: General Informationmentioning
confidence: 99%
“…Natural products are still considered an attractive source of biologically and pharmacologically active compounds [5]. Within a recently conducted multi-disciplinary project on the identification of natural products with anti-inflammatory activity [6], in particular, naturally occurring lignans were quite early identified to exert various kinds of biological activity [7]. As an example, the Edelweiss-derived compound leoligin 29 (Figure 1) inhibits inflammation and selective cell proliferation in vitro and in vivo suggesting its use for the treatment of vein graft disease [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…alpinum, is reported to influence cholesterol metabolism via cholesteryl ester transfer protein (CETP), 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR), and ATP-binding cassette transporters A1 (ABCA1) and G1 (ABCG1) [13][14][15], and is thus an interesting candidate for FXR modulation. In context of an interdisciplinary research program [16] exploiting natural compound isolates towards new potential drug leads [17], we established a stereoselective synthetic route for the generation of a compound library based on the leoligin core structure [18]. In order to identify potential and novel FXR agonists, we utilized FXR specific pharmacophore models [19] to screen a database of leoligin structural analogs.…”
Section: Introductionmentioning
confidence: 99%